2020
DOI: 10.3390/met10010094
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for HAZ Liquation of Nickel-Based Alloy 617B During Gas Tungsten Arc Welding

Abstract: The mechanism for HAZ (heat-affected zone) liquation of alloy 617B during gas tungsten arc welding (GTAW) was investigated. Welding thermal simulation work was conducted to investigate the effects of thermal parameters (peak temperature, holding time, and thermal cycle numbers) on M23C6 carbides’ evolutionary behavior in nickel-based alloy 617B. OM (optical microscopy), SEM (scanning electron microscopy), TEM (transmission electron microscopy), and SIMS (secondary ion mass spectrometry) were employed to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Constitutional liquation occurs during welding or other high-temperature processes, where the melting of components at the grain boundaries of the alloy leads to the formation of a eutectic mixture. Li et al [18,19] suggested that nickel-based alloy 617B will have eutectic microstructure due to constitutional liquation at T p above 1300 °C, basically consistent with their conclusions. Table 3 lists the chemical compositions of points A and B obtained by EDS.…”
Section: Thermal Simulation With Different T Psupporting
confidence: 64%
See 2 more Smart Citations
“…Constitutional liquation occurs during welding or other high-temperature processes, where the melting of components at the grain boundaries of the alloy leads to the formation of a eutectic mixture. Li et al [18,19] suggested that nickel-based alloy 617B will have eutectic microstructure due to constitutional liquation at T p above 1300 °C, basically consistent with their conclusions. Table 3 lists the chemical compositions of points A and B obtained by EDS.…”
Section: Thermal Simulation With Different T Psupporting
confidence: 64%
“…The simulated HAZ with T p of 1450 °C showed contiguous microcracks distributed along the grain boundaries, indicating that the matrix was melted to a large extent. The evolutionary behavior of micron-scale M 23 C 6 carbides during the welding process can explain the liquefaction phenomenon [17][18][19]. The melted structure and micron-scale M 23 C 6 carbide were rich in Ni, Cr, Mo, and Co.…”
Section: Thermal Simulation With Different T Pmentioning
confidence: 98%
See 1 more Smart Citation
“…Schematic description of liquation cracking at γ/MC: (a) pseudo-binary diagram of γ-MC and (b) schematic description of constitutional liquation at γ/MC[16,17,30].…”
mentioning
confidence: 99%